Immigrant Innovators and Firm Performance - Paolo Fornaro; Mika Maliranta; Petri Rouvinen (The Research Institute of the Finnish Economy (ETLA), 2019)
We study immigrants' effects on firm-level innovativeness. Managers, innovators, and other employees are considered as separate groups both in firm employment and in local areas. For each, we estimate the effects of foreignness, the share of immigrants in each group, and diversity, while controlling for an extensive set of employment and other firm characteristics. Pooled cross-section estimates suggest that a higher initial share of immigrant innovators is associated with a subsequently higher probability of a product innovation; the reverse holds for process innovation. In other words, product innovation benefits from a wider spectrum of innovator perspectives brought about by foreign influence, while process innovation suffers from it. The estimated effect for product innovation is modestly large but nevertheless indicates that a host of other covariates besides immigration are important for innovation. When measured by a fractionalization index, diversity among innovators does not promote product innovation. However, culturally the closest groups of migrants have a positive effect, when considered independently. Thus, in our interpretation, diversity does offer some benefits, provided that enough cultural homogeneity of the group is retained.
Keywords: D22; F22; J61; O31; 330; Immigration; Ethnicity; Diversity; Innovation; Knowledge production function; Finland